ROLE OF ICT TOOLS IN SUPPLY CHAIN PERFORMANCE - Apiyo, Rosemary; Kiarie, Dr. David (International Journal of Supply Chain Management, 2018)
Organizations today now require ICT tools that efficient and effective that will give them to access important and relevant information easily and on time so as to enable them to maintain a competitive edge. ICT has enabled interactions between different organizations along the supply chain thus, facilitating data sharing and exchange of information at higher speed and accuracy enabling organizations to meet customer demands on time thus meeting set customer service standards. The need to stay ahead of competition requires organizations to now embrace ICT advancement in their day to day operations. Efficient and effective material handling management can only be achieved with the cooperation of efficient and effective departments within supply chain. The selection of suppliers and negotiation of all aspects of contracts relating to inventory are activities in which purchasing professionals are expected to play a leading role. ERP, MRP, Bar-coding, RFID and DRP have been able to achieve this need and organizations should aspire to include these systems in their supply chain. When ICT tools are well implemented, the company will benefit from them and as a result, the organization will be able to save on costs and eventually make high profits. They will also be able to reduce or eliminate wastes; they will also reduce inventory holding thus releasing capital. Therefore, it is important that, information system researchers continue to research and produce new knowledge that moves the organizations towards current vision of "up to date ICT tools".